2008
DOI: 10.1108/13639510810852567
|View full text |Cite
|
Sign up to set email alerts
|

Police academy training: comparing across curricula

Abstract: Purpose-This study aims to address two interrelated research questions. First, to compare the academy performance of police recruits trained under a traditional academy curriculum with the performance of those trained under a new academy curriculum based on community policing. Second, to investigate whether a different "type" of recruit performs better in the community policing curriculum compared with the traditional curriculum. Design/methodology/approach-Regression analysis is used to estimate the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 26 publications
1
61
0
2
Order By: Relevance
“…General speaking, federal law enforcement agencies and each state legislature institute the basic training frameworks and standards that must be fixed with qualify for a policing requirement (Chappell, 2008). However, to some extent, Kratcoski (2004, p. 17) notes that the actual training can be supported and designed by a training academy administered "by the police agency, by a private training facility, by a state-wide police training academy, or occasionally by a local college or university that has established a program that combines basic training with academic credit that could lead to a higher education degree".…”
Section: Police Training Models In the World And Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…General speaking, federal law enforcement agencies and each state legislature institute the basic training frameworks and standards that must be fixed with qualify for a policing requirement (Chappell, 2008). However, to some extent, Kratcoski (2004, p. 17) notes that the actual training can be supported and designed by a training academy administered "by the police agency, by a private training facility, by a state-wide police training academy, or occasionally by a local college or university that has established a program that combines basic training with academic credit that could lead to a higher education degree".…”
Section: Police Training Models In the World And Regionmentioning
confidence: 99%
“…However, to some extent, Kratcoski (2004, p. 17) notes that the actual training can be supported and designed by a training academy administered "by the police agency, by a private training facility, by a state-wide police training academy, or occasionally by a local college or university that has established a program that combines basic training with academic credit that could lead to a higher education degree". Furthermore, police agencies are likely to connect and contract with colleges/universities/academies to provide some specialized training (Chappell, 2008).…”
Section: Police Training Models In the World And Regionmentioning
confidence: 99%
“…Currently, individual states utilize different methods of training; however, Peace Officer Standards and Training (POST) Academy programs have traditionally offered a behaviorally oriented training curriculum that emphasizes classroom lecture, but includes training scenarios where students must assume specific professional roles and are graded on their performance (Birzer, 2003;Caro, 2011;Chappell, 2007;McCoy, 2006). While many police training programs remain based on a traditional behavioral and militaristic approach (Birzer, 2003), as the community policing model evolves, some academies are experimenting with new training methodologies (Donavant, 2009), or are implementing curricula based on adult learning theory and oriented toward problem-based learning (Knowles, 1988;Werth, 2009Werth, , 2011 to transition from traditional to communityoriented policing (COP) and problem-oriented policing (POP) training models (Birzer, 2003;Chappell, 2007;Werth, 2011). Concurrent with a trend across the USA, Idaho police agencies are proactively seeking ways to strengthen learning organization goals as well as develop community and POP expertise (Crank & Giacomazzi, 2009;Masterson & Stevens, 2001;Russell, 2009;Werth, 2009Werth, , 2011.…”
Section: Police Officer Trainingmentioning
confidence: 99%
“…5 Moreover, the aim of the selection models is to eliminate the candidates whose characteristics or abilities are not acceptable for police work. 6 Exactly because of such importance selection and education have on the one hand, and the development, results monitoring and the possibility of correlating those with work efficiency have on the other, these are highly significant subject matters of all police organisations over the world. 7 Although there are differences between selection models, weighted average and the police work types, the research so far has shown that the majority of the selection models usually consist of health check, cognitive abilities and personality testing, as well as the candidates' physical abilities check.…”
Section: Introductionmentioning
confidence: 99%